Quantum theory of Lee Smolin PS. Recentivism of Józef Bańka - Czerny, Janusz (Folia Philosophica, 2004)
The author focused on a certain ideological analogy between the views of Lee Smolin and Józef Bańka. The idea that contemporary science is included in the paradigm of quasistability, thus indeterminacy, is the essence of this analogy. Bi-furcations, turbulences, attractors, are all determinants of this indeterminacy. There is no other way of examining all these complex phenomena than their «limes» description, thus in the context, which Józef Bańka calls the cognitive context of a «here-now-being». It turns out that this style is binding in the states, which are called the indeterminate states by Ilya Prigogine. This ideological motive was used by the author of the article for a description of natural phenomena.